Perilaku Sosial Tokoh Utama dalam Novel Mbojo Mambure Karya Parange Anaranggana Berdasarkan Perspektif Bourdieu - Izzat Imaniya (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
The purpose of this study is to (1) reveal the social behavior habitus of the main character in the novel Mbojo Mambure by Parange Anaranggana based on Bourdieu's perspective, and (2) identify the domains/arenas of the main character's social behavior in the novel. This study uses a descriptive qualitative approach. The research problem raised is how habitus and arenas can influence the behavior and worldview of the main character in Mbojo Mambure. The data collection technique used is reading and note-taking, while data analysis is conducted using Miles and Huberman’s technique, which includes data reduction, data display, and conclusion drawing. The results of the study show that (1) the social behavior habitus of the main character in this novel includes habits such as gambling, collecting pornographic videos, dressing like a woman, consuming alcohol, and engaging in same-sex relationships; (2) the arenas of the main character’s social behavior consist of the transvestite arena, alcohol addiction arena, prostitution arena, and education arena. This study provides insights into how various social and cultural factors influence the behavior and perspective of the character in the novel.